Evaluation of Work Performance Two Types of Community Tuberculosis Workers in Gianyar Regency - Anak Agung Gede Suputra; I Wayan Gede Artawan Eka Putra; Luh Seri Ani (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: One of the strategies adopted to improve coverage of TB patients (BTA+) in Gianyar Regency is to involve the pakraman (desa adat) TB cadres and the regular (PPTI) TB cadres with four tasks in order to help health care workers to trace and find tuberculosis suspect patients. The purpose of this study was to evaluate work performance between two types of community TB cadres in Gianyar Regency. Methods: This study was an observational research using secondary data of cadres work reports and interview to study participants to understand cadres characteristics and health workers supervision. Numbers of participants were all village TB cadres namely 29 pakraman and 88 regular TB cadres located in Gianyar Regency. Data collection was carried out using questionnaires and observation sheets. Univariate, bivariate and multivariate analysis was conducted. Results: The result shown that work performance of pakraman TB cadres was statistically better than regular TB cadres (adjusted RP=6.1; 95%CI: 3.3-11.2). Better work performance of pakraman TB cadres was found in all four tasks of cadres namely helping education (adjusted RP=7.8; 95%CI: 4.2-14.2), finding tuberculosis suspects (adjusted RP=7.4; 95%CI: 1.7-33.1), tracing of defaulters TB suspects (adjusted RP=17.1; 95%CI: 1.8-166.4) and tracing loss of follow up TB patients (adjusted RP=3.8x108; 95%CI: (1.6-8.9)x108). Conclusion: Work performance of pakraman TB cadres was better than regular TB cadres in all four tasks.